Effect of different composition of biomass on co-pelletization of waste wood - Nur Fatihah, Shakri (2024)
In this study, the effect of different composition of biomass on co-pelletization of waste wood are discussed in order to produce the biomass pellet with high quality of characteristic. The biomass used is Meranti and Seraya waste wood. Initially, the waste woods were ground and sieve with diameter ranging 0.5 mm to 1.0 mm to reduce the size of sample. Next, the sample was undergoing torrefaction process with temperature 270ºC for 30 minutes. Then, the torrefied sample undergo pelletization process by using hot press machine and produce biomass pellet with different composition which is 100:0, 25:75, 50:50, 75:25, and 0:100 of co-pelletization meranti:seraya. Two different binding agents were added which is 8% Glycerol and 25% Palm Oil Mill Effluent (POME) sludge. The sample produced were analyse with 7 different analysis, including tensile strength, higher heating value, ash content, moisture content, density, combustion and Fourier transform Infrared Spectroscopy (FTIR) to evaluate the characteristic of the biomass pellet.All of that analysis were conducted to determine the characteristics of pellets, with the highest quality pellet selected being 75:25 Meranti:Seraya with Glycerol as a binding agent. The study found that pellets with lower ash content and moisture content, such as 75:25 Meranti:Seraya, prevent air pollution during combustion. Pellets with higher moisture content release fewer pollutants into the air, improving air quality and reducing carbon emissions. The highest higher heating value (HHV) was found in 75:25 Meranti:Seraya pellets, resulting in increased energy efficiency. The highest tensile strength was found in 100% Meranti pellets, enhancing durability and handling efficiency. The 75:25 pellets also showed good results during combustion due to longer flame lengths, lower ignition time, and longer time for char oxidation. These pellets meet the ISO standard for high quality pellets and can be effectively bound with glycerol compared to POME.